Vulnerability to Stunting in the West African Sahel - Alfani, Federica (Elsevier, 2020)
This paper presents a simple simulation framework for understanding and analyzing vulnerability to stunting. We utilize Demographic and Health Surveys merged with satellite data on climatic shocks. Children aged 0–5 years are grouped into three categories: consistently stunted, vulnerable, and non-vulnerable. The first group constitutes those who are stunted and will also be stunted in any hypothetical period. Non-vulnerable are those whose likelihood to be stunted is zero. The vulnerable face a probability between 0 and 1 of being stunted. The probability is calculated as the share of years in which the child would be stunted, given the village level distribution of weather shocks over the period 2000–2013. We provide estimates of vulnerability to stunting in Burkina Faso, Northern Ghana, Mali, Northern Nigeria, and Senegal by aggregating over villages, districts and countries.